Academic writing course. Time, space and focus - Torres-Salinas, Daniel (Infonomy, 2024)
In this first text of a series of four, we address several preliminary aspects that should be considered before embarking on any academic writing process. Specifically, we will discuss three aspects. Firstly, we will explore the optimal time of day for writing and how to plan our writing sessions. Secondly, we will highlight the importance of having a properly configured personal workspace. Thirdly, we emphasize the significance of the concept of "Deep Work," recommending techniques for focus related to setting up our virtual desktop, managing ambient sounds, and incorporating meditation.